Reforming Public-Private Partnerships in Railway Services: Learning from the Jakarta Monorail Project Debacle - Arafia, Diantha (PT Penjaminan Infrastruktur Indonesia (Persero), 2024)
Public-Private Partnerships (PPPs) offer a promising strategy for accelerating railway infrastructure development, yet they entail significant risks if not executed correctly. Indonesia has adopted PPPs since the 1990s, but their impact on railway services remains underexplored. This paper suggests improvements to Indonesia’s railway PPP mechanism to improve effectiveness, efficiency, and service deliverability. It argues that the effectiveness of railway PPPs is hindered by the public sector’s limited capacity and weak regulatory and institutional frameworks. The research employs a case study of the Jakarta Monorail project, terminated in 2015 after 11 years of problematic development. The research methods include literature reviews and a comparative analysis of the case with two prominent railway PPPs in other developing countries: the Bangkok Transit System in Thailand and the Delhi Mass Rapid Transit System Phase I in India. The findings lead to two key recommendations for the government: reorganizing the roles and coordination processes of key PPP agencies and establishing a continuous capacity-building scheme for PPP stakeholders. These recommendations may create a more supportive environment for PPPs, thereby increasing the likelihood of successful railway PPP implementation in Indonesia.